Evaluation of performance of two different chest tubes with either a sharp or a blunt tip for thoracostomy in 100 human cadavers - Ortner Clemens M; Ruetzler Kurt; Schaumann Nikolaus; Lorenz Veit; Schellongowski Peter; Schuster Ernst; Salem Ramez M; Frass Michael (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2012)
Abstract Background Emergent placement of a chest tube is a potentially life-saving procedure, but rate of misplacement and organ injury is up to 30%. In principle, chest tube insertion can be performed by using Trocar or Non-trocar techniques. If using trocar technique, two different chest tubes (equipped with sharp or blunt tip) are currently commercially available. This study was performed to detect any difference with respect to time until tube insertion, to success and to misplacement rate. Methods Twenty emergency physicians performed five tube thoracostomies using both blunt and sharp tipped tube kits in 100 fresh human cadavers (100 thoracostomies with each kit). Time until tube insertion served as primary outcome. Complications and success rate were examined by pathological dissection and served as further outcomes parameters. Results Difference in mean time until tube insertion (63s vs. 59s) was statistically not significant. In both groups, time for insertion decreased from the 1st to the 5th attempt and showed dependency on the cadaver's BMI and on the individual physician. Success rate differed between both groups (92% using blunt vs. 86% using sharp tipped kits) and injuries and misplacements occurred significantly more frequently using chest tubes with sharp tips (p = 0.04). Conclusion Data suggest that chest drain insertion with trocars is associated with a 6-14% operator-related complication rate. No difference in average time could be found. However, misplacements and organ injuries occurred more frequently using sharp tips. Consequently, if using a trocar technique, the use of blunt tipped kits is recommended.